Animating heritage: the Sidek family in roles in cultural branding and retail engagement - Mohd Radzol, Aifa Rozaini; Ibrahim, Norshamsiah; Hassan, Suchi; Che Shalifullizam, Ida Fatihah (Faculty of Art and Design, 2025)
The Sidek family legacy in Malaysian badminton has transcended sports, evolving into a powerful cultural brand through its animated series, Anak-anak Sidek. This study explores how the visual narrative of the Sidek brothers, rooted in perseverance, discipline, and national pride has been leveraged to shape cultural branding and consumer experiences across retail contexts, both online and offline. The biographical comic and the animation series of Anak-anak Sidek has immortalized the family’s journey and is also seen as a strategic tool for identity formation, a symbol of national pride and fostering emotional connections with audiences. Drawing parallels to global franchises like Upin & Ipin and Boboiboy, the Sidek animation exemplifies how local art can drive commercial success, from merchandise and memorabilia to digital platforms. The popularity of the animation has spurred demand for Sidek-branded products, such as comics, apparel, and badminton equipment, sold in physical stores. The recent retrospective experiential marketing like exhibition at the Sultan Alam Shah Museum transformed the story into an immersive retail experience where visitors engaged with trophies, stamps and interactive displays which could enhance emotional connection to the brand. This study highlights the Sidek Family’s role in redefining national identity through visual arts and branding.